Meta-Analysis of Environmental Impacts on Nitrous Oxide Release in Response to N Amendment - Aronson, Emma; Allison, Steven D. (Frontiers in Microbiology, 2012)
Atmospheric nitrous oxide (N2O) accounts for approximately 5% of the global greenhouse effect and destroys stratospheric ozone. Soils are the most important source of N2O, which is produced during nitrification and denitrification. To assess the impact of environmental variables and ecosystems on N2O flux, we performed a meta-analysis comparing N2O flux in N amended and matched control plots in non-agricultural soils. We found that N2O release increased with N amendment in the short term. Although there were few studies in shrubland, this ecosystem showed the greatest response. The N2O response to N amendment was greater in year-round studies and in studies with more measurements, but lower in longer studies. The N2O response was greater at higher latitudes and precipitation rates. We also observed an unexpected 55% decline in the N2O response to N amendment over the 23 years covered by the studies. This pattern may reflect a suppression of the N2O response from long-term N deposition accumulation, particularly in temperate regions. Although short-term increases in reactive N entering natural systems may cause positive feedbacks to the release of N2O, this effect may diminish over time in locations with high rates of N deposition.